The Incidence of Thyroid Gland Invasion in Patients with Carcinoma of the Larynx who Underwent Total Laryngectomy - A, Mawaddah; S, See-Sze; MB, Marina; KC, Pua; M, Abdullah-Sani (IIUM Medical Journal Malaysia, 2019)
Introduction: Total thyroidectomy or at least hemithyroidectomy is routinely performed alongside total laryngectomy in patients with advanced carcinoma of the larynx. Life-threatening hypocalcaemia and hypothyroidism are common sequelae especially with adjuvant radiation. The study aims to determine the incidence of microscopic thyroid gland invasion and challenge the idea of routine thyroidectomy in advanced carcinoma of the larynx. Materials and Methods: This study was a retrospective observational study. It was done in two tertiary centres in Malaysia between 2003 and 2013 for a total duration of 11 years. A total of 72 patients were included in this study. Data from medical records, operative notes, and histopathological reports were collected and analysed. Results: Three patients (4.2%) had the presence of microscopic thyroid gland invasion. There were no significant associations between microscopic thyroid gland invasion and tumour subsites, histological types of a tumour nor T staging (p>0.05) Conclusion: The incidence of microscopic thyroid gland invasion in advance carcinoma of the larynx is low, disavowing routine thyroidectomy. Limitations: Some factors such as cartilage invasion on CT imaging and central lymph node treatment were not considered due to limitations in case documentation.